Comparing and constrasting two integral management plans for fishing resources from a political ecology perspective: The case of Pearl Lagoon, SAAR, Nicaragua / Dennis Mairena Arauz - Mairena Arauz, Dennis (Nicaragua : URACCAN)
The fishermen and their organisation, theoretical framework originn of political ecology the debate on political ecology options, political ecology in Pearl Laoon is the current political ecology in Pearl Lagoon sustainable? a sketch, an analysis of management plans, CAMP-LAB and DIPAL comparative analysus and contrat between CAMP-LAB and DIPAL management plans for Pearl Lagoon Basin. Col. Mon
Contents, table, bibliography
Keywords: 1. THESIS AND DISSERTATIONES 2. PLANS FISHING RESOURCES 3. POLITICAL ECOLOGY 4. THESIS FISHING